2021
DOI: 10.1007/s00508-021-01973-1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic deep vein thromboses in prolonged hospitalized COVID-19 patients

Abstract: High incidence of venous thromboembolic (VTE) events in coronavirus disease 2019 (COVID-19) patients has been reported despite pharmacologic thromboprophylaxis. We performed prospective bilateral lower extremity ultrasound evaluation of prolonged hospitalized COVID-19 ward patients from our institution without clinical suspicion of deep vein thrombosis (DVT). A total of 102 patient were included in the study. All patients were receiving pharmacologic thromboprophylaxis, the majority in intermediate or therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…Among 102 patients without clinically overt DVT, asymptomatic DVT was detected in 25.5% patients despite all patients receiving thromboprophylaxis. The frequency of DVT reached 60% in mechanical ventilation survivors ( 24 ), which confirmed previously published reports. Thus, the more thromboses are searched for, the more they are discovered.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among 102 patients without clinically overt DVT, asymptomatic DVT was detected in 25.5% patients despite all patients receiving thromboprophylaxis. The frequency of DVT reached 60% in mechanical ventilation survivors ( 24 ), which confirmed previously published reports. Thus, the more thromboses are searched for, the more they are discovered.…”
Section: Discussionsupporting
confidence: 91%
“…Known thrombophilia is a reported predictive factor for both asymptomatic thromboses ( 24 ) and VTE in general, as shown in the current study. However, the definition of thrombophilia status is vague and hard to quickly obtain, even if patients were previously tested or are currently suspected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, in seven out of eight cases, it was only a distal DVT giving an incidence of proximal DVT of 2.3%. More recent studies confirm the low prevalence of asymptomatic proximal DVT [ 13 , 14 ]. In conclusion, all besides one study showed a low incidence of proximal DVT outside the ICU.…”
Section: Discussionmentioning
confidence: 80%
“…All scores had somewhat better properties for DVT then PE discrimination which might reflect the challenges of PE diagnosis in COVID-19 patients that might be not sufficiently stable to undergo diagnostic procedures. DVT evaluation is more easily performed and often unexpectedly high event rates are encountered if screening of asymptomatic patients can be utilized [10] . In contrast to VTE that associates with more severe COVID-19 presentation and high functional impairment, AT seem to be associated with milder severity of COVID-19 symptoms and more clear clinical presentation, often in the context of previously established chronic metabolic comorbidities [4] .…”
mentioning
confidence: 99%